Negative electrode for lithium secondary battery and lithium secondary battery including the same
The controlled alignment of carbon-based active material in the negative electrode layer of lithium secondary batteries addresses lithium precipitation and dendrite formation, enhancing safety and efficiency under high-rate conditions by maintaining a stable N/P ratio and reducing electrical resistance.
Patent Information
- Application Number
- JP2024541707
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-05-15
- Filing Date
- 2023-09-15
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-09-15
AI Technical Summary
Lithium secondary batteries experience lithium precipitation and dendrite formation near the negative electrode tab during high-rate conditions, leading to increased electrical resistance and safety risks due to the reversal of the N/P ratio.
A negative electrode design with a carbon-based active layer that has a controlled alignment gradient, where the alignment of carbon-based negative electrode active material increases from the first region to the n-th region, using a magnetic field to align the a-b axis crystal planes of graphite perpendicular to the negative electrode current collector, reducing electrical resistance and preventing lithium precipitation.
The design effectively suppresses lithium precipitation and maintains high efficiency during long-term high-rate charging and discharging, improving battery safety by maintaining a stable N/P ratio and reducing electrical resistance near the negative electrode tab.
Smart Images

Figure 2025502179000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0116896 filed on September 16, 2022 and Korean Patent Application No. 10-2023-0062320 filed on May 15, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.
[0002] The present invention relates to a negative electrode for a lithium secondary battery in which lithium deposition during charging and discharging is suppressed, and a lithium secondary battery including the same. [Background technology]
[0003] 2. Description of the Related Art In recent years, secondary batteries have been widely used not only in small devices such as portable electronic devices, but also in medium- to large-sized devices such as battery packs for hybrid and electric vehicles and power storage devices.
[0004] Such secondary batteries are power generating elements capable of being charged and discharged and have a laminated structure of a positive electrode / separator / negative electrode. In general, the positive electrode contains a lithium metal oxide as a positive electrode active material, and the negative electrode contains a carbon-based negative electrode active material such as graphite. During charging, lithium ions released from the positive electrode are absorbed into the carbon-based negative electrode active material of the negative electrode, and during discharging, the lithium ions contained in the carbon-based negative electrode active material are absorbed into the lithium metal oxide of the positive electrode, thereby allowing repeated charging and discharging.
[0005] One of the factors that influence the performance of a secondary battery is the capacity ratio of the active materials contained in the positive and negative electrodes. The capacity ratio can be expressed as the N / P ratio. The N / P ratio is the value obtained by dividing the total capacity of the negative electrode calculated by considering the capacity per unit area of the negative electrode by the total capacity of the positive electrode calculated by considering the capacity per unit area of the positive electrode, and since it has a significant effect on the safety and capacity of the battery, it is generally adjusted to have a value of 1 or more.
[0006] In relation to this, in recent years, as a method for increasing the energy density of secondary batteries, there has been a trend to reduce the weight and / or thickness of structures that do not generate capacity in the electrodes, i.e., electrode tabs, exterior materials, separators, current collectors, etc., and increase the weight and / or thickness of structures that generate capacity, e.g., electrode active layers, etc. Such changes have the effect of increasing the oxidation-reduction reaction rate in the electrode tabs, where electrons move smoothly during charging and discharging of the battery.
[0007] However, such promotion of the redox reaction promotes deterioration near the negative electrode tab, and the accelerated deterioration near the negative electrode tab induces an increase in resistance, resulting in a decrease in capacity in the region adjacent to the negative electrode tab. That is, an inversion phenomenon occurs in which the N / P ratio becomes smaller than 1 in the region adjacent to the negative electrode tab. When the N / P ratio becomes smaller than 1, lithium ions are not fully intercalated into the negative electrode active material during charging of the battery, but are precipitated on the surface of the negative electrode to form dendrites. The possibility of dendrites occurring increases significantly, particularly when the lithium secondary battery is used for a long time under high-rate conditions. The dendrites thus formed may induce an internal short circuit in the battery, and may act as a factor that impairs the safety of the battery. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Korean Patent Publication No. 10-2015-0028457 [Patent Document 2] Korean Patent Publication No. 10-2016-0125720 Summary of the Invention [Problem to be solved by the invention]
[0009] An object of the present invention is to provide a negative electrode for a lithium secondary battery in which lithium precipitation at the end of the negative electrode mixture layer is suppressed even when the lithium secondary battery is used for a long period of time under high-rate conditions, and a lithium secondary battery including the same. [Means for solving the problem]
[0010] To solve the above-mentioned problems, In one embodiment, the present invention comprises: a negative electrode active layer provided on at least one surface of a negative electrode current collector and including a carbon-based negative electrode active material; and a negative electrode tab extended to one side of the negative electrode active layer and provided on a non-coated portion of the negative electrode current collector that does not include the negative electrode active layer, The negative electrode active layer has the same length ratio to the entire length based on a thickness direction cross-sectional structure having a negative electrode tab on one side, and is divided into a first region to an nth region (2≦n≦10) sequentially arranged from a first side portion from which the negative electrode tab is drawn to a second side portion opposite thereto, and the degree of alignment of the carbon-based negative electrode active material represented by the following Formula 1 increases from the first region to the nth region.
[0011]
number
[0012]
number
[0013]
number
[0014] In formulas 1 to 3, S 60 / 0 is the peak intensity ratio (I0 B / A ) when the X-ray incidence angle is 60° (I60 B / A ), I60A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 60°, I60 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 60°, I0 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 0°, I0 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 0°.
[0015] In this case, the first region of the negative electrode active layer has an alignment degree (S 60 / 0 ) can be 0.01 to 1.0.
[0016] In addition, in the negative electrode active layer, the degree of alignment of the carbon-based negative electrode active material represented by the following formula 4 may increase from the first region to the nth region.
[0017] [Formula 4] OI=I 004 / I 110
[0018] In Equation 4, I 004 represents the area of the peak showing the (0,0,4) crystal plane in X-ray diffraction (XRD) spectroscopy analysis of the negative electrode active layer, I 110 represents the area of the peak indicating the (1,1,0) crystal plane in X-ray diffraction (XRD) spectroscopy analysis of the negative electrode active layer.
[0019] In addition, the carbon-based negative electrode active material contained in the nth region has an alignment degree (OI nth The degree of alignment (OI) of the carbon-based negative electrode active material contained in the first region 1st ) can be 110% to 300%.
[0020] In addition, the first region of the negative electrode active layer has an average alignment degree (OI 1st ) may be 0.1 to 0.6.
[0021] In addition, the negative electrode active layer has a degree of alignment (S 60 / 0 ) and / or the degree of alignment (OI) of the carbon-based negative electrode active material according to the above formula 4 may have an increasing gradient from the first region to the nth region, or may tend to increase stepwise at predetermined intervals.
[0022] In addition, the first region of the negative electrode active layer has a ratio (I 004 / I 002 ) may be 0.04 or greater.
[0023] Meanwhile, the carbon-based negative electrode active material may include at least one of natural graphite and artificial graphite, and in this case, the carbon-based negative electrode active material may have a sphericity of 0.75 or more.
[0024] Further, in one embodiment, the present invention provides There is provided a lithium secondary battery comprising an electrode assembly including a positive electrode, the above-described negative electrode according to the present invention, and a separator disposed between the positive electrode and the negative electrode.
[0025] In this case, the positive electrode may include a positive electrode tab including a positive electrode active layer provided on at least one surface of a positive electrode current collector and including one or more positive electrode active materials selected from lithium metal oxides represented by the following Chemical Formula 1 and Chemical Formula 2.
[0026] [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O2
[0027] [Chemical formula 2] LiM2 p Mn 1-p O4
[0028] In the above Chemical Formula 1 and Chemical Formula 2, M 1 is one or more of the elements W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, and v are 1.0≦x≦1.30, 0.5≦y<1, 0 <z≦0.3、0<w≦0.3、0≦v≦0.1であり、かつy+z+w+v=1であり、 M 2 is Ni, Co or Fe, p is in the range of 0.05≦p≦1.0.
[0029] Specifically, the positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O 2、 LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O2, LiNi 0.7 Mn 1.3 O4, LiNi 0.5 Mn 1.5 O4, LiNi 0.3 Mn 1.7 O4, LiFePO4, LiFe 0.8 Mn 0.2 PO4, and LiFe 0.5 Mn 0.5 It may contain one or more of the following:
[0030] Also, the electrode assembly may be a stacked electrode assembly, a zigzag electrode assembly, or a zigzag-stack electrode assembly. Effect of the Invention
[0031] The negative electrode for a lithium secondary battery according to the present invention has a degree of alignment (S 60 / 0 and / or OI) to reduce the electrode resistance, thereby exhibiting high efficiency during charging and discharging of the secondary battery, especially during long-term charging and discharging under high-rate conditions, and also having an excellent effect of suppressing lithium deposition at the end of the negative electrode active layer, which is advantageous in terms of battery safety. [Brief description of the drawings]
[0032] [Figure 1] 1A is a cross-sectional view of the negative electrode; FIG. 1B is a plan view of the negative electrode; and FIG. 1C is a plan view showing the position of the negative electrode in the negative electrode slurry state during the production of the negative electrode. [Diagram 2] 13 is an image showing the alignment of the ab-axis crystal planes of graphite depending on whether or not a magnetic field is applied to a negative electrode slurry during the formation of a negative electrode active layer, where (a) shows the case where no magnetic field is applied and the graphite crystal planes are not aligned, and (b) shows the case where a magnetic field is applied and the graphite crystal planes are aligned. [Diagram 3] This is an image showing the tendency of the type and position of each orbital absorption peak depending on the angle of incidence of X-rays during near-edge X-ray absorption fine structure (NEXAFS) spectroscopy. (a) shows the type and position of the orbital that forms the double bond of graphite, and (b) shows the peak shape of each orbital position when X-rays are incident. [Figure 4] 1 is an image showing an incident angle of X-rays during Near Edge X-ray Absorption Fine Structure (NEXAFS) spectroscopy analysis of a negative electrode manufactured according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0033] Since the present invention can be modified in various ways and can have various embodiments, a specific embodiment will be described in detail.
[0034] However, this is not intended to limit the invention to any particular embodiment, but it should be understood to include all modifications, equivalents, or alternatives falling within the spirit and scope of the invention.
[0035] In the present invention, terms such as "comprise" and "have" are intended to specify the presence of features, numbers, steps, operations, components, parts, or combinations thereof described in the specification, and may be understood as not precluding the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.
[0036] In addition, in the present invention, when a layer, film, region, plate, or other portion is described as being "on" another portion, this includes not only the case where it is "directly on" the other portion, but also the case where there is another portion in between. Conversely, when a layer, film, region, plate, or other portion is described as being "under" the other portion, this includes not only the case where it is "directly under" the other portion, but also the case where there is another portion in between. In addition, in the present application, being "on" can include not only the case where it is located at the top, but also the case where it is located at the bottom.
[0037] In addition, in the present invention, "containing as a main component" may mean containing 50% by weight or more (or 50% by volume or more), 60% by weight or more (or 60% by volume or more), 70% by weight or more (or 70% by volume or more), 80% by weight or more (or 80% by volume or more), 90% by weight or more (or 90% by volume or more), or 95% by weight or more (or 95% by volume or more) of a defined component based on the total weight (or total volume). For example, "containing graphite as a main component as a negative electrode active material" may mean containing 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more, or 95% by weight or more of graphite based on the total weight of the negative electrode active material, and in some cases, it may mean that the entire negative electrode active material is made of graphite and contains 100% by weight of graphite.
[0038] In addition, in the present invention, the "cross-sectional structure" refers to a structure of a surface cut in the thickness direction of the negative electrode active layer, or a structure of a surface cut perpendicularly based on the surface of the negative electrode active layer. In this case, the cut surface may be the same as a surface cut perpendicularly to the process direction when forming the negative electrode active layer, or a surface cut in the width direction of the negative electrode slurry applied to form the negative electrode active layer. In addition, the cross-sectional structure may refer to a structure of a surface cut in the thickness direction of the negative electrode active layer, and a structure cut in a direction proceeding from one surface where the negative electrode tab is formed to the opposite surface.
[0039] In addition, in this specification, "the carbon-based negative electrode active material is oriented" or "the carbon-based negative electrode active material is aligned" may mean that a specific crystal plane (e.g., the ab-axis crystal plane of graphite) showing a two-dimensional planar structure of the carbon-based negative electrode active material constituting the negative electrode active material particles is arranged to have a predetermined inclination based on the surface of the negative electrode current collector, as shown in (b) of Figure 2. This may be different from (a) of Figure 2, in which the particles of the carbon-based negative electrode active material themselves are aligned in a predetermined direction only inside the negative electrode active layer, but have no directionality with respect to the negative electrode current collector.
[0040] In addition, "high orientation of the carbon-based negative electrode active material" may mean that a specific crystal plane (e.g., the ab-axis crystal plane of graphite) showing a two-dimensional planar structure of the carbon-based negative electrode active material contained in the negative electrode active layer has a high frequency of having a certain inclination with respect to the surface of the negative electrode current collector. In some cases, it may mean that the crystal plane of the carbon-based negative electrode active material contained in the negative electrode active layer is aligned at a high angle (e.g., an angle close to vertical, more than 45°, specifically 60° or more) with respect to the surface of the negative electrode current collector.
[0041] In addition, the term "high degree of alignment of the carbon-based negative electrode active material" refers to the "degree of alignment (S 60 / 0 and / or OI)” is large, and it may mean that a specific crystal plane (e.g., the ab-axis crystal plane of graphite) showing a two-dimensional planar structure of the carbon-based negative electrode active material contained in the negative electrode active layer is aligned at a low angle (e.g., less than 45°) with respect to the surface of the negative electrode current collector. Conversely, “the carbon-based negative electrode active material has a low degree of alignment” means that the “degree of alignment (S 60 / 0 and / or OI)” has a small value, which may mean that the crystal plane of the carbon-based negative electrode active material contained in the negative electrode active layer is aligned at a high angle (e.g., an angle close to perpendicular, 45° or more, specifically 60° or more) with respect to the surface of the negative electrode current collector.
[0042] Furthermore, in this specification, the term "average particle size (D 50 ) refers to the particle size at which the cumulative value in the particle size distribution of the particles is 50%, and is also called the median diameter.
[0043] The present invention will now be described in more detail.
[0044] <Negative electrodes for lithium secondary batteries> In one embodiment, the present invention comprises: a negative electrode active layer provided on at least one surface of a negative electrode current collector and including a carbon-based negative electrode active material; and a negative electrode tab extended to one side of the negative electrode active layer and provided on a non-coated portion of the negative electrode current collector that does not include the negative electrode active layer, The negative electrode active layer has the same length ratio to the entire length based on a thickness direction cross-sectional structure having a negative electrode tab on one side, and is divided into a first region to an nth region (2≦n≦10) sequentially arranged from a first side portion from which the negative electrode tab is drawn to a second side portion opposite thereto, and the degree of alignment of the carbon-based negative electrode active material represented by the following Formula 1 increases from the first region to the nth region, thereby providing a negative electrode for a lithium secondary battery.
[0045]
number
[0046] The negative electrode for a lithium secondary battery according to the present invention includes a negative electrode active layer including a carbon-based negative electrode active material on at least one surface of a negative electrode current collector, and a negative electrode tab located at one end of a surface of the negative electrode current collector on which the negative electrode active layer is provided, and provided in a non-coated portion on which the negative electrode active layer is not provided.
[0047] Here, the negative electrode active layer refers to a layer that realizes the electrical activity of the negative electrode. The negative electrode active layer includes a carbon-based negative electrode active material as a negative electrode active material in order to realize electrical activity through a reversible oxidation-reduction reaction during charging and discharging of the battery. Specifically, the carbon-based negative electrode active material means a material mainly composed of carbon atoms, and such a carbon-based negative electrode active material may include graphite. The graphite may include at least one of natural graphite and artificial graphite. For example, the carbon-based negative electrode active material may include natural graphite or artificial graphite alone, or may include a mixture of natural graphite and artificial graphite in some cases. In this case, the mixture ratio of natural graphite and artificial graphite may be 5 to 40:60 to 95, or 10 to 30:70 to 90, based on weight. The carbon-based negative electrode active material contains natural graphite and artificial graphite in the above-mentioned mixing ratio, and thus can realize high orientation of the carbon-based negative electrode active material on the surface of the negative electrode current collector while strengthening adhesion between the negative electrode current collector and the negative electrode active layer.
[0048] The carbon-based negative electrode active material is preferably a spherical graphite granule formed by the aggregation of a plurality of flake graphite. Examples of flake graphite include natural graphite, artificial graphite, mesophase calcined carbon (bulk mesophase) made from tar and pitch, graphitized cokes (raw coke, green coke, pitch coke, needle coke, petroleum coke, etc.), etc. In particular, a graphite granule assembled from a plurality of highly crystalline natural graphites is preferable. In addition, one graphite granule may be formed by the aggregation of 2 to 100 flake graphite particles, preferably 3 to 20 flake graphite particles.
[0049] Such a carbon-based negative electrode active material, specifically, graphite, may have a spherical particle shape, and the sphericity of the graphite particles may be 0.75 or more, for example, 0.75 to 1.0, 0.75 to 0.95, 0.8 to 0.95, or 0.90 to 0.99. Here, the "sphericity" may refer to the ratio of the shortest diameter (minor axis) to the longest diameter (major axis) among any diameters passing through the center of the particle, and when the sphericity is 1, it means that the particle shape is spherical. The sphericity may be measured using a particle shape analyzer, or may be determined by measuring the particle shape using a scanning electron microscope (SEM) or an energy dispersive spectrometer, and then analyzing the measurement results. The present invention has the advantages that, by realizing a nearly spherical shape of the carbon-based negative electrode active material, the electrical conductivity of the negative electrode active layer can be increased, thereby improving the capacity of the battery, and that, by increasing the specific surface area per unit weight of the negative electrode active material, the adhesive strength between the negative electrode active layer and the current collector can be improved.
[0050] In addition, the carbon-based negative electrode active material has an average particle size (D 50 ), specifically, the average particle size (D 50 ) can be shown.
[0051] The average particle size of the carbon-based negative electrode active material, which is close to a sphere, may be advantageously small in order to maximize the degree of disorder in the direction of expansion of each particle so as to prevent the particles from expanding due to charging with lithium ions. However, if the particle size of the carbon-based negative electrode active material is less than 0.5 μm, a large amount of binder is required due to the increase in the number of particles per unit volume, and the sphericity and sphericity yield may be low. On the other hand, if the maximum particle size exceeds 10 μm, the expansion rate of the negative electrode active material during charging and discharging of the secondary battery increases significantly, and the adhesion between the particles and the adhesion between the negative electrode active material particles and the current collector may decrease due to repeated charging and discharging, resulting in a significant decrease in cycle characteristics.
[0052] In addition, the negative electrode active layer may be prepared by applying a negative electrode slurry including a carbon-based negative electrode active material to at least one surface of a negative electrode current collector, followed by drying and rolling the same, in order to realize electrical activity through a reversible oxidation-reduction reaction during charging and discharging of the secondary battery.
[0053] FIG. 1 is a structural diagram showing the structure of a negative electrode according to the present invention, in which (a) is a cross-sectional view of the negative electrode, (b) is a plan view of the negative electrode, and (c) is a plan view showing the position of the negative electrode in the state of a negative electrode slurry during the production of the negative electrode.
[0054] 1, the negative electrode according to the present invention includes a negative electrode active layer 120 formed on at least one surface of a negative electrode current collector 110. The negative electrode also includes a negative electrode tab 111 electrically connected to a negative electrode terminal, at one end of the negative electrode current collector 110 on which the negative electrode active layer 120 is provided, and the negative electrode tab 111 is provided in a blank portion that does not include the negative electrode active layer 120 on its surface, which realizes electrical activity, in order to be electrically connected to a negative electrode tab of another adjacent negative electrode and / or a negative electrode terminal of another adjacent negative electrode when assembling an electrode for manufacturing a secondary battery.
[0055] 1(a) and 1(b), the negative electrode active layer 120 includes a first side surface S1 of the negative electrode active layer from which the negative electrode tab 111 is drawn based on the surface, a second side surface S2 disposed on the other side of the first side surface facing the first side surface, and a third side surface S3 and a fourth side surface S4 connected to the first side surface S1 and the second side surface S2 to form a single surface. Here, the second side surface S2 to the fourth side surface S4 may be slit (S / F) after drying the negative electrode slurry 120′ during the manufacture of the negative electrode as shown in FIG. 1(c), and the end portions may have the shape of a cut surface, but are not limited thereto.
[0056] In addition, the negative electrode active layer 120 is divided into a plurality of regions, and the carbon-based negative electrode active material contained in the regions may have different inclinations of the ab-axis crystal plane of the carbon-based negative electrode active material with respect to the surface of the negative electrode current collector. Specifically, the negative electrode active layer 120 has a thickness direction cross-sectional structure in which the negative electrode tab 111 is provided on one side, as shown in FIG. 1(a), with respect to the total length L, and the thickness direction cross-sectional structure has the same length ratio (L1=L2=...=L n-1 =L n ), and is divided into a first region (121-1) to an n-th region (121-n, where 2≦n≦10) sequentially arranged from a first side surface portion S1 from which the negative electrode tab 111 is drawn to a second side surface portion S2 opposing thereto. For example, when the negative electrode active layer 120 includes three regions (n=3), the first region 121-1, the second region 121-2, and the third region 121-3 are sequentially arranged from the first side surface portion S1 from which the negative electrode tab 111 is drawn to the second side surface portion S2 opposing thereto, and the lengths of the regions may be the same (L1=L2=L3).
[0057] The present invention can reduce the deviation between the alignment degree of the carbon-based negative electrode active material contained in a given region and the alignment degree of the carbon-based negative electrode active material contained in a region adjacent to the given region by dividing the negative electrode active layer 120 into a plurality of regions having the same length ratio. A large deviation in the alignment degree of the carbon-based negative electrode active material in a given region compared to the adjacent region means that the inclination change of the ab-axis crystal plane of the carbon-based negative electrode active material with respect to the surface of the negative electrode current collector is large. Such a negative electrode has low electrolyte impregnation, and the mobility of lithium ions during high-rate charging and discharging may decrease, thereby reducing the electrical properties of the negative electrode. Therefore, the present invention can reduce the deviation in the alignment degree of the carbon-based negative electrode active material between each region by dividing the negative electrode active layer into a plurality of regions having the same length ratio.
[0058] For this purpose, the negative electrode active layer may be divided into 2 to 10 regions (2≦n≦10), specifically, 3 to 10 regions (3≦n≦10), 5 to 10 regions (5≦n≦10), 7 to 10 regions (7≦n≦10), 2 to 8 regions (2≦n≦8), 2 to 6 regions (2≦n≦6), or 2 to 4 regions (2≦n≦4).
[0059] Furthermore, the present invention can suppress lithium deposition at the end of the negative electrode composite layer even when the lithium secondary battery is used for a long time under high rate conditions by controlling the alignment of the carbon-based negative electrode active material included in the negative electrode active layer for each region. Specifically, the negative electrode active layer according to the present invention has a degree of alignment (S 60 / 0 and / or OI) may be increased.
[0060] In general, in an electrode tab where electrons move smoothly during charging and discharging of a battery, the oxidation-reduction reaction is promoted, and the reaction rate tends to increase. The promotion of the oxidation-reduction reaction promotes deterioration near the negative electrode tab, and the accelerated deterioration near the negative electrode tab induces an increase in electrical resistance, resulting in a decrease in capacity in the area adjacent to the negative electrode tab. As a result, a reversal phenomenon occurs in which the N / P ratio is less than 1 in the area of the negative electrode active layer adjacent to the negative electrode tab. When the N / P ratio is less than 1, lithium is precipitated on the surface of the negative electrode to form dendrites. The possibility of the dendrites occurring increases significantly, particularly when a lithium secondary battery is used for a long time under high-rate conditions, and the dendrites formed in this way can cause an internal short circuit in the battery, thereby acting as a factor that impairs the safety of the battery.
[0061] However, in the present invention, the inclination of the ab-axis crystal plane of the carbon-based negative electrode active material with respect to the surface of the negative electrode current collector increases as the ab-axis crystal plane of the carbon-based negative electrode active material approaches the first side portion of the negative electrode active layer provided on the side where the negative electrode tab is drawn out. This can reduce the electrical resistance of the region of the negative electrode active layer adjacent to the negative electrode tab, thereby preventing lithium from being deposited in a dendritic shape on the surface of the negative electrode during charging and discharging. Specifically, the ab-axis crystal plane of the carbon-based negative electrode active material contained in the first side portion from which the negative electrode tab is drawn out, more specifically, the first region closest to the negative electrode tab, can be aligned nearly perpendicular to the negative electrode current collector. In addition, the ab-axis crystal plane of the carbon-based negative electrode active material contained in each region tends to increase in distance from the negative electrode tab as it progresses from the first region to the nth region (where 2≦n≦10), and the inclination of the ab-axis crystal plane of the carbon-based negative electrode active material contained in each region tends to decrease as the distance from the negative electrode tab increases. The decrease in the inclination of the ab-axis crystal plane of the carbon-based negative electrode active material (i.e., the degree of alignment (S 60 / 0 and / or an increase in OI) may show a stepwise decrease (or increase in the degree of alignment) trend or a decreasing gradient (or an increasing gradient of the degree of alignment) as one progresses from the first region to the nth region (where 2≦n≦10).
[0062] Here, "the carbon-based negative electrode active material is aligned nearly perpendicular to the negative electrode current collector" may mean that the crystal plane of the carbon-based negative electrode active material constituting the spherical particles, specifically, the ab-axis crystal plane indicating the planar direction of graphite having a two-dimensional structure among the crystal planes of graphite, is aligned and arranged at an inclination nearly perpendicular to the surface of the negative electrode current collector. In this case, the planar direction of the graphite (i.e., the ab-axis crystal plane direction) may have an average inclination of 60° to 120°, preferably 70° to 110°, or 80° to 100°, relative to the negative electrode current collector.
[0063] In addition, the alignment of the carbon-based negative electrode active material may be performed by any method commonly used in the art, without any particular limitations. Specifically, after applying a negative electrode slurry containing a carbon-based negative electrode active material to a surface of a negative electrode current collector, a magnetic field is applied to the surface of the negative electrode slurry at the upper and lower parts of the negative electrode slurry, and the strength and / or application time of the magnetic field is decreased as the position changes from a first region to an nth region (2≦n≦10) of the negative electrode active layer. In this way, the degree of alignment of the carbon-based negative electrode active material may be increased as the position moves from the first region to the nth region.
[0064] As an example, when the negative electrode active layer is divided into a total of three regions (n=3) from the first side portion where the negative electrode tab is drawn to the second side portion, the magnetic field strength may be applied to the negative electrode slurry surface corresponding to the first region, the second region, and the third region at 2.0T, 1.0T, and 0.5T, respectively, so that the magnetic field strength is reduced stepwise during the preparation of the negative electrode active layer. In this case, the degree of alignment (S 60 / 0 and / or OI) may be implemented in the order of first region < second region < third region.
[0065] As another example, when the negative electrode active layer is divided into a total of five regions (n=5) from the first side portion where the negative electrode tab is drawn to the second side portion, a magnetic field of 2.0T→0.5T may be applied to the negative electrode slurry surface corresponding to the first to fifth regions during the manufacture of the negative electrode active layer so as to provide a magnetic field strength gradient. In this case, the degree of alignment (S 60 / 0and / or OI) may embody an alignment gradient in the order of first region<second region<third region<fourth region<fifth region.
[0066] In the present invention, the magnetic field application to the negative electrode slurry may be performed at an intensity of 0.5T to 2.0T for 1 to 60 seconds, specifically at an intensity of 0.5T to 1.0T, 0.5T to 1.5T, 1.0T to 2.0T, 0.8T to 1.5T, or 0.8T to 1.2T for 1 to 30 seconds, or 1 to 20 seconds. By controlling the intensity and application time of the magnetic field applied to the negative electrode slurry as described above, the alignment degree (S 60 / 0 and / or OI difference, which can prevent an increase in electrical resistance in the region adjacent to the negative electrode tab during charging and discharging, and can prevent the N / P ratio from being reversed.
[0067] In addition, the magnetic field strength may be applied so that the magnetic field strength deviation between any region of the negative electrode slurry and the region adjacent thereto is not large. For example, the magnetic field strength applied to any region may have a deviation of 0.01T to 0.5T from the magnetic field strength applied to the region adjacent thereto, specifically, 0.01T to 0.3T, 0.01T to 0.1T, 0.1T to 0.5T, or 0.2T to 0.3T. The applied magnetic field strength affects the alignment degree of the carbon-based negative electrode active material. Therefore, if the magnetic field strength deviation between any region and the region adjacent thereto becomes large, the alignment degree deviation of the carbon-based negative electrode active material contained therein may become large. At the point where the alignment degree deviation of the carbon-based negative electrode active material is large, the impregnation of the electrolyte may be low, and the mobility of lithium ions during high-rate charge and discharge may be reduced. Therefore, by controlling the magnetic field strength deviation applied to any region and the region adjacent thereto to be small when the magnetic field is applied to the negative electrode slurry, such a problem may be overcome.
[0068] Meanwhile, the degree of alignment of the carbon-based negative active material contained in the negative active layer can be determined by molecular orientation and / or crystal structure analysis of the carbon-based negative active material.
[0069] As one example, in the negative electrode active layer, the carbon-based negative electrode active material is aligned nearly perpendicular to the negative electrode current collector, and in near-edge X-ray absorption fine structure (NEXAFS) spectroscopy analysis, the value according to the following Equation 1 may increase as the measurement position changes from a first region to an nth region (where 2≦n≦10).
[0070]
number
[0071] (In the above formula 1, S 60 / 0 is the peak intensity ratio (I0 B / A ) when the X-ray incidence angle is 60° (I60 B / A ) value.
[0072] Unlike X-ray photoelectron spectroscopy (XPS), which measures the bond energy between atoms constituting a compound, near-edge X-ray absorption fine structure (NEXAFS) spectroscopy can only reflect the local structure near the carbon atom including the excited core electron and the surface structure of the particles of the measured carbon-based negative electrode active material. Therefore, the present invention uses a spectrum obtained by NEXAFS spectroscopy on the negative electrode active layer to measure the degree of alignment (S 60 / 0 ) can be measured.
[0073] Specifically, when X-rays are irradiated onto the carbon atom (C) of a carbon-based negative electrode active material, the occupied electrons (K-shell inner-shell electrons) present in the inner-shell level (1s orbital) of the carbon atom absorb the X-ray energy and are excited to various unoccupied molecular orbitals, and NEXAFS spectroscopy uses the absorption spectrum observed at this time.
[0074] Here, in the case of graphite, which is a carbon-based negative electrode active material, the above-mentioned vacant level molecular orbitals include i) the π* orbital which belongs to the antibonding orbital of the sp2 bond which reflects the crystallinity (basal plane, orientation, etc.) of graphite, ii) the σ* orbital which belongs to the antibonding orbital of the sp3 bond which reflects the crystallinity disorder (edge plane, non-orientation, etc.), and iii) the Rydberg which belongs to the antibonding orbital of a C-H bond or a C-O bond.
[0075] Carbon-based negative electrode active materials, such as graphite, have a crystal structure in which carbon atoms are stacked in a hexagonal network structure (see FIG. 3(a)) formed by sp2 bonds, with the two-dimensional plane (ab-axis crystal plane) of the hexagonal network surface being the basal plane, and the surface showing the end of the hexagonal network (c-axis crystal plane) being the edge plane. The edge plane of the carbon-based negative electrode active material may have a high sp3 bond ratio because -COOH, -C=O, etc. may be present in the terminal carbon. Therefore, the crystal plane orientation and / or alignment of the carbon-based negative electrode active material can be analyzed by analyzing the state of the sp2 orbitals of the carbon atoms in each crystal plane of the carbon-based negative electrode active material.
[0076] The NEXAFS spectroscopy may be performed by a total electron yield method in which the negative electrode active layer is irradiated with X-rays having a fixed angle of incidence with respect to the negative electrode active layer, and the energy of the irradiated X-rays is scanned from 280 eV to 320 eV to measure the sample current flowing through the sample to supplement the photoelectrons emitted from the surface of the negative electrode active layer. At this time, since the synchrotron radiation is X-rays linearly polarized by applying a magnetic field E, the intensity of the absorption peak observed depending on the direction of incidence of the X-rays may differ. Specifically, referring to FIG. 3(a), in the case of graphite, which is a carbon-based negative electrode active material, it has a hexagonal network structure via sp2 bonds (-C=C-) of carbon atoms, and the sp2 bonds include a σ orbital located parallel to the sp2 bonds and a π orbital located perpendicular to the sp2 bonds. Here, the σ orbital and π orbital have a symmetric structure with a node at the nucleus position of the carbon atom and the σ* orbital and π* orbital, which are antibonding orbitals, respectively, so the σ* orbital and π* orbital have the same directionality as the σ orbital and π orbital.
[0077] Therefore, as shown in FIG. 3(b), when the incidence direction of X-rays is parallel to the sp2 bond, the intensity of the absorption peak excited from the 1s level of carbon to the π* level becomes large, and conversely, when it is perpendicular to the sp2 bond, the intensity of the absorption peak becomes small. On the other hand, when the incidence direction of X-rays is parallel to the sp2 bond, the intensity of the absorption peak excited from the 1s level to the σ* level of carbon becomes small, and conversely, when it is perpendicular to the sp2 bond, the intensity of the absorption peak becomes large. Due to these characteristics, when the orientation of the graphite contained in the negative electrode active layer is high as shown in FIG. 2(b), the antibonding vacant molecular orbital of the graphite located on the surface of the negative electrode active layer is uniformly aligned, so that when the incidence angle of X-rays to the negative electrode active layer is changed, the spectrum shape changes significantly due to reinforcement and interference of the emitted photoelectrons. In contrast, when the orientation of the graphite contained in the negative electrode active layer is low, as shown in Figure 2(a), the vacant antibonding molecular orbitals of the graphite located on the surface of the negative electrode active layer are non-uniformly aligned, so that the spectral shape hardly changes even if the incident angle of the X-rays on the sample is changed.
[0078] In the present invention, in order to measure the degree of orientation of the carbon-based negative electrode active material contained in the negative electrode active layer, a NEXAFS spectroscopy analysis is performed on the surface of the negative electrode active layer, and X-rays are incident on the negative electrode active layer at different incident angles (0° and 60°). The ratio of the intensity of the absorption peak (peak B = 293 ± 0.2 eV) attributable to the transition from the 1s level to the σ* level of carbon to the intensity of the absorption peak (peak A = 287 ± 0.2 eV) attributable to the transition from the 1s level to the π* level of carbon for each incident angle (I B / A ), the ratio of the intensity ratio between the incidence angles (60° and 0°) (S 60 / 0 =I60 B / A / I0 B / A ) to determine the orientation and / or alignment degree (S 60 / 0 ) can be quantitatively measured.
[0079] That is, the degree of orientation of the carbon-based negative electrode active material contained in the first region is expressed by i) the intensity (I60 A ) for the absorption peak (peak B = 293 ± 0.2 eV) intensity attributable to the transition from the 1s level of carbon to the σ* level (I60 B ) percentage (I60 B / A ) was calculated, and ii) the absorption peak (peak A = 287 ± 0.2 eV) intensity (I0 A ) for the absorption peak (peak B = 293 ± 0.2 eV) intensity attributable to the transition from the 1s level to the σ* level of carbon (I0 B ) percentage (I0 B / A ) and then iii) calculate their ratio (S 60 / 0 =I60 B / A / I0 B / A ) can be evaluated.
[0080]
number
[0081]
number
[0082] In Equation 2 and Equation 3, I60 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 60°, I60 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 60°, I0 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 0°, I0 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 0°.
[0083] Here, the above formula 1(S 60 / 0 ) may mean that the closer to 1, the lower the orientation of the ab-axis crystal plane of graphite, which is a carbon-based negative electrode active material, with respect to the negative electrode current collector, and the higher the degree of order (OI), and that the closer to 0, the higher the orientation of the ab-axis crystal plane of graphite with respect to the negative electrode current collector, and the lower the degree of order (OI). The first region according to the present invention is a region in which the value (S 60 / 0 ) may be 1.0 or less, and more specifically may be 0.9 or less, 0.8 or less, 0.7 or less, 0.5 or less, 0.01 to 1.0, 0.05 to 0.7, 0.05 to 0.5, 0.05 to 0.4, 0.1 to 0.7, 0.3 to 0.7, or 0.5 to 0.8. In addition, the nth region may be a region having a value (S 60 / 0 ) may be greater than 0.8, and more specifically may be greater than 0.9, 0.8 to 2.0, 0.9 to 1.5, 0.8 to 1.5, 0.8 to 1.3, or 0.85 to 1.2.
[0084] The first region of the negative electrode active layer according to the present invention is represented by the formula 1 (S 60 / 0 ) being 1 or less indicates that the ab-axis crystal plane of the carbon-based negative electrode active material contained in the first region is aligned nearly perpendicular to the negative electrode current collector as shown in Figure 2(b). Therefore, a negative electrode including the same can prevent an increase in electrical resistance in the region adjacent to the negative electrode tab during charging and discharging of a secondary battery, and can prevent an inversion of the N / P ratio.
[0085] This is also because the particles of the carbon-based negative electrode active material are 60 / 0 ) is 1 or less. 60 / 0) being 1 or less means that the ab-axis crystal planes of molecular crystals forming the particles of the carbon-based anode active material are aligned with a predetermined directionality within the particles. Therefore, when such a carbon-based anode active material is included in the anode active layer, the ab-axis crystal planes of the carbon-based anode active material tend to be non-oriented with respect to the surface of the anode current collector as shown in Figure 2(a) unless a separate treatment is performed, and this is differentiated from the first region of the anode active layer according to the present invention.
[0086] In another example, in the first region of the negative electrode active layer, the ab-axis crystal plane of the carbon-based negative electrode active material is aligned nearly perpendicular to the negative electrode current collector, and the degree of alignment (OI) of the carbon-based negative electrode active material, as represented by the following Equation 4, is obtained by X-ray diffraction (XRD) spectroscopy analysis: 1st The degree of alignment (OI) of the carbon-based negative electrode active material contained in the nth region (where 2≦n≦10) nth ), which may result in an increase in the degree of alignment (OI) of the carbon-based negative electrode active material as the position of the negative electrode active layer changes from the first side portion to the second side portion.
[0087] [Formula 4] OI=I 004 / I 110
[0088] In Equation 4, I 004 represents the area of the peak showing the (0,0,4) crystal plane in X-ray diffraction (XRD) spectroscopy analysis of the negative electrode active layer, I 110 represents the area of the peak indicating the (1,1,0) crystal plane in X-ray diffraction (XRD) spectroscopy analysis of the negative electrode active layer.
[0089] The crystal plane orientation of the carbon-based negative electrode active material can be determined by a crystal plane analysis of the carbon-based negative electrode active material, such as X-ray diffraction spectroscopy. The degree of alignment (OI) of the carbon-based negative electrode active material represented by the above formula 4 can be an index indicating the direction in which the crystal structure of the carbon-based negative electrode active material is aligned during X-ray diffraction measurement, specifically, the degree to which the ab-axis crystal plane indicating the two-dimensional planar structure of the carbon-based negative electrode active material is aligned with respect to the surface of the negative electrode current collector. For example, when the negative electrode active layer contains graphite as the carbon-based negative electrode active material, the negative electrode active layer exhibits 2θ=26.5±0.2°, 42.4±0.2°, 43.4±0.2°, 44.6±0.2°, 54.7±0.2°, and 77.5±0.2°, which are peaks for graphite during X-ray diffraction spectroscopy analysis. This refers to the (0,0,2) plane, (1,0,0) plane, (1,0,1)R plane, (1,0,1)H plane, (0,0,4) plane, and (1,1,0) plane of the graphite crystal planes contained in the negative electrode active layer. In general, in the case of graphite, graphene layers are placed on the a-axis and b-axis planes, and such graphene layers are stacked along the c-axis to have a hexagonal or rhombohedral crystal structure. Here, the crystal plane peak is a peak that indicates the plane characteristics of such a crystal structure. In addition, the peak that appears at 2θ=43.4±0.2° may be considered to have appeared due to overlap of the (1,0,1)R plane of the carbon-based material and the peak corresponding to the (1,1,1) plane of the current collector, for example, Cu.
[0090] In the present invention, the degree of alignment (OI) of graphite can be measured by the area ratio of the peak at 2θ=77.5±0.2° indicating the [1,1,0] plane and the peak at 2θ=54.7±0.2° indicating the [0,0,4] plane, specifically, the area ratio obtained by integrating the intensities of the above peaks. In addition, the X-ray diffraction was measured using CuKα radiation as a target line, and the target line was extracted and measured using a monochromator device to improve the peak intensity resolution. At this time, the measurement conditions were 2θ=10°-90°, a scan speed (° / s) of 0.044-0.089, and a step size of 0.026° / step. In addition, the (0,0,4) plane appearing at 2θ=54.7±0.2° indicates the thickness direction characteristic (c-axis direction characteristic) of the layered structure in which the two-dimensional planar structures of the graphite layers are stacked, and the (1,1,0) plane appearing at 2θ=77.5±0.2° indicates the planar characteristic (ab-axis direction characteristic) of the stacked graphite layers. Therefore, the smaller the (0,0,4) plane peak indicating the thickness direction characteristic of the graphite layer plane, and the larger the (1,1,0) plane peak indicating the planar characteristic of the graphite layer, the higher the angle at which the graphite plane is aligned with respect to the negative electrode current collector surface. In other words, the closer the OI value is to 0, the closer the angle or inclination of the graphite layer surface to the negative electrode current collector surface is to 90°, and the larger the OI value is, the closer the inclination to the negative electrode current collector surface is to 0° or 180°.
[0091] In this aspect, in the first region of the negative electrode active layer according to the present invention, since the ab-axis crystal plane of the carbon-based negative electrode active material is aligned nearly perpendicular to the negative electrode current collector, the degree of alignment (OI) of the carbon-based negative electrode active material may be lower than that of the nth region (where 2≦n≦10) of the negative electrode active layer.
[0092] Specifically, the degree of alignment (OI) of the carbon-based negative electrode active material contained in the first region may be 0.1 to 0.6, more specifically, 0.15 to 0.6, 0.15 to 0.5, 0.2 to 0.5, 0.2 to 0.4, 0.25 to 0.45, 0.3 to 0.5, or 0.35 to 0.6.
[0093] In addition, the degree of alignment (OI) of the carbon-based negative electrode active material contained in the nth region nth ) is the degree of alignment (OI) of the carbon-based negative electrode active material contained in the first region. 1st ), and more specifically, 101% to 280%, 101% to 260%, 101% to 240%, 101% to 230%, 101% to 220%, 101% to 200%, 150% to 250%, 160% to 230%, 180% to 270%, 185% to 225%, 170% to 25 It can be 0%, 105%-130%, 110%-150%, 110%-130%, 120%-180%, 120%-160%, 101%-180%, 150%-200%, 125%-150%, 140%-180%, 160%-190%, 110%-160%, or 120%-150%.
[0094] Furthermore, the average degree of alignment (OI) of the carbon-based negative electrode active material contained in the entire negative electrode active layer may be 0.4 to 1.2, specifically, 0.4 to 1.0, 0.4 to 0.9, 0.4 to 0.7, 0.4 to 0.6, 0.6 to 1.0, 0.8 to 1.0, or 0.5 to 0.8.
[0095] The present invention relates to a method for determining the degree of alignment (OI) of the carbon-based negative electrode active material contained in the first region, the nth region, and the entire negative electrode active layer. 1st and O.I. nth By controlling the above-mentioned, the lithium ion mobility in the negative electrode active layer adjacent to the negative electrode tab during charging and discharging of the battery can be improved while the electrical resistance of the electrode can be reduced, thereby preventing a decrease in the charge and discharge capacity in the first region adjacent to the negative electrode tab. This can prevent the reversal of the N / P ratio in the first side portion adjacent to the negative electrode tab, thereby preventing lithium precipitation.
[0096] In addition, the negative electrode active layer may have an average degree of alignment (OI) of 0.1 to 0.5, specifically, 0.2 to 0.4. By controlling the average value of the overall orientation of the negative electrode active layer within the above range, the present invention can maintain a constant alignment of the carbon-based negative electrode active material contained throughout the negative electrode active layer, thereby achieving uniform electrical properties of the negative electrode.
[0097] Furthermore, in order to prevent lithium from being precipitated in a dendritic form on the surface of the negative electrode active layer during charging and discharging of the battery at a high rate, the first region of the negative electrode active layer is formed by adjusting the intensity of the peak representing the (0,0,4) crystal plane and the intensity ratio of the peak representing the (0,0,2) crystal plane (I 004 / I 002 Specifically, the first region can control the intensity ratio (I 004 / I 002 The present invention relates to a method for determining the intensity ratio (I ) of a peak indicating a (0,0,4) crystal plane to a peak indicating a (0,0,2) crystal plane among peaks detected during X-ray diffraction (XRD) spectroscopic analysis. 004 / I 002 ) within the above range, an increase in the DC internal resistance in the first region can be suppressed, and there are advantages in that the high rate characteristics are improved and the cycle life characteristics are improved.
[0098] Meanwhile, the negative electrode active layer according to the present invention may further selectively contain a conductive material, a binder, other additives, and the like, in addition to the negative electrode active material, as necessary.
[0099] The conductive material may include, but is not limited to, one or more of carbon black, acetylene black, ketjen black, carbon nanotubes, carbon fibers, and the like.
[0100] For example, the negative electrode active layer may contain carbon black, carbon nanotubes, carbon fibers, etc., alone or in combination, as a conductive material.
[0101] At this time, the content of the conductive material may be 0.1 parts by weight to 10 parts by weight, specifically 0.1 parts by weight to 8 parts by weight, 0.1 parts by weight to 5 parts by weight, 0.1 parts by weight to 3 parts by weight, or 0.5 parts by weight to 2 parts by weight, based on 100 parts by weight of the total negative electrode active layer. By controlling the content of the conductive material within the above range, the present invention can prevent the negative electrode resistance from increasing due to a low content of conductive material, resulting in a decrease in charge capacity. In addition, it can prevent problems such as a decrease in the content of the negative electrode active material due to an excessive amount of conductive material, resulting in a decrease in charge capacity, or a decrease in rapid charge characteristics due to an increase in the loading amount of the negative electrode active layer.
[0102] In addition, the binder is a component that aids in bonding between the active material and the conductive material and the current collector, and may be suitably used within a range that does not deteriorate the electrical properties of the electrode. Specifically, the binder may include any one or more of vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, and fluororubber.
[0103] The content of the binder may be 0.1 to 10 parts by weight, specifically 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, or 2 to 6 parts by weight, based on 100 parts by weight of the total negative electrode active layer. By controlling the content of the binder contained in the negative electrode active layer within the above range, the present invention can prevent a decrease in adhesive strength of the active layer due to a low content of the binder, or a decrease in electrical properties of the electrode due to an excessive amount of the binder.
[0104] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, nickel, titanium, calcined carbon, etc., and in the case of copper or stainless steel, it may be surface-treated with carbon, nickel, titanium, silver, etc. The average thickness of the negative electrode current collector may be suitably 1 μm to 500 μm, taking into consideration the conductivity and total thickness of the negative electrode to be manufactured.
[0105] The negative electrode for a lithium secondary battery according to the present invention has the above-described configuration and is therefore excellent in the effect of suppressing lithium deposition on the surface of the negative electrode active layer during charging and discharging of the secondary battery, particularly during charging and discharging under high-rate conditions, and thus a lithium secondary battery including the negative electrode has the advantage of exhibiting high safety.
[0106] <Lithium secondary battery> In one embodiment, the present invention further comprises: There is provided a lithium secondary battery comprising an electrode assembly including a positive electrode, the above-described negative electrode of the present invention, and a separator disposed between the positive electrode and the negative electrode.
[0107] The lithium secondary battery according to the present invention includes an electrode assembly in which a plurality of positive electrodes and a plurality of negative electrodes are alternately arranged with a separator disposed therebetween, and an electrolyte composition in the form of a lithium salt and an electrolyte additive dissolved in a non-aqueous organic solvent. The lithium secondary battery includes the negative electrode of the present invention in which the ab-axis crystal plane of the carbon-based negative electrode active material contained in the region adjacent to the negative electrode tab in the negative electrode active layer is aligned perpendicularly and / or nearly perpendicularly with respect to the surface of the negative electrode current collector. As a result, the lithium secondary battery has the advantage of being highly safe since lithium deposition is prevented on the surface of the negative electrode active layer, especially on the surface of the region adjacent to the negative electrode tab, during charging and discharging of the battery, especially during charging and discharging under high rate conditions.
[0108] At this time, the negative electrode has the same structure as that described above, and therefore a detailed description thereof will be omitted.
[0109] In addition, the positive electrode includes a positive electrode active layer prepared by applying a slurry containing a positive electrode active material onto a positive electrode current collector, followed by drying and pressing. If necessary, the positive electrode active layer may further selectively include a conductive material, a binder, other additives, and the like.
[0110] The positive electrode active material is a material capable of electrochemically reacting on a positive electrode current collector, and may include at least one of lithium metal oxides represented by the following Chemical Formula 1 and Chemical Formula 2 capable of reversibly intercalating and deintercalating lithium ions.
[0111] [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O2
[0112] [Chemical formula 2] LiM 2 p Mn q P r O4
[0113] In the above Chemical Formula 1 and Chemical Formula 2, M 1 is one or more of the elements W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, and v are 1.0≦x≦1.30, 0.5≦y<1, 0 <z≦0.3、0<w≦0.3、0≦v≦0.1であり、かつy+z+w+v=1であり、 M 2 is Ni, Co or Fe, p is 0.05≦p≦1.0, q is 1-p or 2-p; r is 0 or 1.
[0114] The lithium metal oxides represented by Chemical Formula 1 and Chemical Formula 2 above are materials containing high amounts of nickel (Ni) and manganese (Mn), respectively, and when used as a positive electrode active material, have the advantage of being capable of stably supplying high capacity and / or high voltage electricity.
[0115] In this case, the lithium metal oxide represented by the above chemical formula 1 is LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O 2、 LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O2, etc., and the lithium metal oxide represented by the above chemical formula 2 is LiNi 0.7 Mn 1.3 O4, LiNi 0.5 Mn 1.5 O 4、 LiNi 0.3 Mn 1.7 O 4、 LiFePO4, LiFe 0.8 Mn 0.2 PO4, LiFe 0.5 Mn 0.5 PO4, etc., which may be used alone or in combination.
[0116] The positive electrode active material may be included in an amount of 85 parts by weight or more, specifically 90 parts by weight or more, 93 parts by weight or more, or 95 parts by weight or more, based on the weight of the positive electrode active layer.
[0117] The positive electrode active layer may further include a conductive material, a binder, and other additives in addition to the positive electrode active material.
[0118] In this case, the conductive material is used to improve the electrical performance of the positive electrode, and may be any conductive material commonly used in the art. Specifically, the conductive material may include one or more of natural graphite, artificial graphite, carbon black, acetylene black, denka black, ketjen black, super P, channel black, furnace black, lamp black, thermal black, graphene, and carbon nanotubes.
[0119] The conductive material may be included in an amount of 0.1 to 5 parts by weight based on the weight of each positive electrode active layer, specifically 0.1 to 4 parts by weight, 2 to 4 parts by weight, 1.5 to 5 parts by weight, 1 to 3 parts by weight, 0.1 to 2 parts by weight, or 0.1 to 1 part by weight.
[0120] In addition, the binder plays a role of binding the positive electrode active material, the positive electrode additive, and the conductive material to each other, and may be used without any particular limitation as long as it has such a function. Specifically, the binder may include one or more resins selected from polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethylmethacrylate, and copolymers thereof. As an example, the binder may include polyvinylidene fluoride.
[0121] The binder may be included in an amount of 1 to 10 parts by weight, specifically 2 to 8 parts by weight, or 1 to 5 parts by weight, based on the weight of each positive electrode active layer.
[0122] The total thickness of the positive electrode active layer is not particularly limited, but may be specifically 50 μm to 300 μm, more specifically 100 μm to 200 μm, 80 μm to 150 μm, 120 μm to 170 μm, 150 μm to 300 μm, 200 μm to 300 μm, or 150 μm to 190 μm.
[0123] In addition, the positive electrode may use a positive electrode current collector having high conductivity without inducing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, etc. may be used, and in the case of aluminum or stainless steel, those surface-treated with carbon, nickel, titanium, silver, etc. may also be used. In addition, the average thickness of the current collector may be suitably applied to be 3 μm to 500 μm, taking into consideration the conductivity and total thickness of the positive electrode to be manufactured.
[0124] Meanwhile, the separator interposed between the positive and negative electrodes of each unit cell is an insulating thin film having high ion permeability and mechanical strength, and is not particularly limited as long as it is one commonly used in the art, specifically, one containing at least one polymer selected from polypropylene, polyethylene, and polyethylene-propylene copolymers having chemical resistance and hydrophobicity may be used. The separator may have a porous polymer substrate such as a sheet or nonwoven fabric containing the above-mentioned polymer, and may have a composite separator formed by coating organic or inorganic particles on the porous polymer substrate with an organic binder. The separator may have an average pore diameter of 0.01 μm to 10 μm and an average thickness of 5 μm to 300 μm.
[0125] Meanwhile, the lithium secondary battery according to the present invention is not particularly limited, but may be a secondary battery having a form including a stack type, a zigzag type, or a zigzag-stack type electrode assembly. As one example, the lithium secondary battery according to the present invention may be a pouch type secondary battery or a prismatic type secondary battery.
[0126] The negative electrode applied to the lithium secondary battery according to the present invention has a degree of alignment (S 60 / 0 By implementing a low OI, it is possible to improve the lithium ion mobility in the first region adjacent to the negative electrode tab during charging and discharging of the battery and reduce the electrical resistance, thereby preventing a decrease in the charge and discharge capacity per unit area of the region. This prevents the reversal of the N / P ratio that occurs in the negative electrode active layer adjacent to the negative electrode tab during high-rate charging and discharging, thereby preventing lithium precipitation. Therefore, the lithium secondary battery has the advantages of being highly safe and capable of being charged and discharged for long periods of time under high-rate conditions.
[0127] The present invention will now be described in more detail with reference to examples and experimental examples.
[0128] However, the following examples and experimental examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples and experimental examples.
[0129] <Examples 1 to 4. Production of negative electrodes for lithium secondary batteries> Natural graphite was prepared as the negative electrode active material, carbon black was prepared as the conductive material, and carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) were prepared as the binder. The sphericity of the natural graphite was adjusted as shown in Table 1 below. 95 parts by weight of natural graphite, 1 part by weight of carbon black, 1.5 parts by weight of carboxymethyl cellulose (CMC), and 2.5 parts by weight of styrene butadiene rubber (SBR) were mixed with water to a solid content of 50% to form a negative electrode slurry, which was then cast onto a copper sheet (thickness: 10 μm) being transported in a roll-to-roll manner.
[0130] Then, four magnets having the same size were arranged in succession so as to be perpendicular to the moving direction of the applied negative electrode slurry (i.e., in the width direction of the negative electrode slurry). At this time, the magnetic field was applied so that the magnetic field strength applied to the magnets changed from the first side part of the negative electrode slurry, which is the negative electrode active layer provided with the negative electrode tab, to the second side part, which is the other side, as shown in Table 1, (a) stepped at a predetermined interval from 2.0 T to 1.0 T, or (b) had a decreasing gradient, thereby inducing the orientation of natural graphite in the negative electrode slurry. In addition, the time for applying the magnetic field to the upper surface of the negative electrode slurry was adjusted to 5 seconds. Then, the copper sheet coated with the negative electrode slurry was dried in a vacuum oven at 130°C, and rolled to a density of 1.63±0.2 g / cc, and slitting and notching were performed successively so that the negative electrode tab was provided on the side where the first side part was located, to manufacture the negative electrode.
[0131] In order to confirm the alignment of the carbon-based negative active material in each region of the negative active layer of each manufactured negative electrode, the negative active layer was divided into first to fourth regions (n=4) from the first side portion where the negative tab was located to the second side portion on the other side, and each region had the same length ratio to the total length of the negative active layer. The lengths of the first to fourth regions were the same as the size of the magnet used to apply the magnetic field. Then, i) near-edge X-ray absorption fine structure (NEXAFS) spectroscopy and X-ray diffraction (XRD) spectroscopy were performed on each region of the negative active layer of each manufactured negative electrode, and spectra were measured. The degree of alignment (S 60 / 0 and OI) were calculated and are shown in Table 1 below. ii) From the spectrum obtained when X-ray diffraction (XRD) spectroscopy was performed on the first region of the negative electrode active layer, the ratio of the peak intensity indicating the (0,0,4) plane to the peak intensity indicating the (0,0,2) plane (I 004 / I 002 ) was calculated and is shown in Table 2 below.
[0132]
number
[0133]
number
[0134]
number
[0135] In formulas 1 to 3, S 60 / 0 is the peak intensity ratio (I0 B / A ) when the X-ray incidence angle is 60° (I60 B / A ), I60 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 60°, I60 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 60°, I0 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 0°, I0 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 0°.
[0136] [Formula 4] OI=I 004 / I 110
[0137] In Equation 4, I 004 represents the area of the peak showing the (0,0,4) crystal plane in X-ray diffraction (XRD) spectroscopy analysis of the negative electrode active layer, I 110represents the area of the peak indicating the (1,1,0) crystal plane in X-ray diffraction (XRD) spectroscopy analysis of the negative electrode active layer.
[0138] [Table 1]
[0139] [Table 2]
[0140] The measurement conditions for the near-edge X-ray absorption fine structure (NEXAFS) and X-ray diffraction (XRD) are as follows.
[0141] (1) Near-edge X-ray absorption fine structure (NEXAFS) -Accelerating voltage: 1.0GeV~1.5GeV -Storage current: 80mA~350mA - Angle of incidence: 60° or 0°
[0142] (2) X-ray diffraction (XRD) - Target: Cu (Kα-ray) graphite monochromator -Slit: Divergence slit = 1 degree, Receiving slit = 0.1mm, Scattering slit = 1 degree
[0143] <Comparative Examples 1 to 3. Production of negative electrodes for lithium secondary batteries> A negative electrode for a lithium secondary battery was prepared by carrying out the same method as in Example 1, except that no magnetic field was applied to the surface of the negative electrode slurry coated on the copper sheet, or a magnetic field of 1.0 T or 2.0 T was applied without changing the magnetic field strength.
[0144] In this case, i) the sphericity of the carbon-based negative electrode active material, ii) the degree of alignment (S 60 / 0 and OI), and iii) the ratio of the peak intensity representing the (0,0,4) plane to the peak intensity representing the (0,0,2) plane calculated from X-ray diffraction (XRD) (I004 / I 002 ) are shown in Table 3 below.
[0145] [Table 3]
[0146] <Examples 5 to 8 and Comparative Examples 4 to 6. Production of Lithium Secondary Batteries> The positive electrode active material is LiNi with a particle size of 5 μm. 0.7 Co 0.1 Mn 0.1 Al 0.1 O2 was prepared and mixed with polyvinylidene fluoride as a carbon-based conductive material and binder in N-methylpyrrolidone (NMP) in a weight ratio of 94:3:3 to form a slurry, which was then cast onto an aluminum sheet, dried in a vacuum oven at 120°C, and rolled to produce a positive electrode.
[0147] A separator made of polypropylene having a thickness of 18 μm was interposed between the obtained positive electrode and the negative electrode prepared in each of the examples and comparative examples, and the resulting positive electrode was inserted into a case, and then an electrolyte composition was injected to assemble a lithium secondary battery.
[0148] The type of negative electrode applied to each lithium secondary battery is shown in Table 4 below.
[0149] [Table 4]
[0150] <Experimental Example 1> In order to evaluate the safety of the lithium secondary battery according to the present invention during high-rate charging and discharging, the following experiments were carried out on the lithium secondary batteries manufactured in the examples and comparative examples.
[0151] B) High-rate characteristics evaluation of secondary batteries First, each of the manufactured lithium secondary batteries was initially charged. Specifically, the lithium secondary batteries were initially charged at a temperature of 25° C. with a charging current of 0.3 C to a charge cut-off voltage of 4.2 V to 4.25 V, and the current density at the cut-off voltage was continued until it reached 0.02 C, thereby activating the batteries.
[0152] Each activated lithium secondary battery was fully charged at room temperature (22°C) at 0.1C-rate. The fully charged lithium secondary battery was then discharged at 0.1C-rate to measure the initial discharge capacity. Then, each lithium secondary battery was fully charged again at 0.1C-rate and discharged at 1.0C, 2.0C, 5.0C, and 9.0C-rates to measure the relative discharge capacity ratio based on the initial discharge capacity for each discharge rate. The measured discharge capacity ratios are shown in Table 5.
[0153] B) Safety evaluation of secondary batteries First, each of the manufactured lithium secondary batteries was initially charged. Specifically, the lithium secondary batteries were initially charged at a temperature of 25° C. with a charging current of 0.3 C to a charge cut-off voltage of 4.2 V to 4.25 V, and the current density at the cut-off voltage was continued until it reached 0.02 C, thereby activating the batteries.
[0154] Thereafter, each activated lithium secondary battery was charged at a temperature of 25°C with a charge current of 3.0C to a charge cut-off voltage of 4.2V to 4.25V, and discharged in a constant current mode until the current density at the cut-off voltage was 0.02C. Such charge / discharge was counted as one cycle, and a total of 100 cycles were performed. Each lithium secondary battery that had been charged / discharged 100 times was disassembled to confirm lithium deposition on the negative electrode surface. The results are shown in Table 5.
[0155] [Table 5]
[0156] As shown in Table 5 above, it was found that the secondary battery including the negative electrode for lithium secondary batteries according to the present invention not only has excellent high-rate charge / discharge efficiency, but also suppresses lithium metal deposition on the negative electrode surface even when repeatedly charged at high rates.
[0157] This means that the degree of orientation in which the carbon-based negative electrode active material is aligned nearly perpendicular to the surface of the negative electrode current collector is greatly induced in the first region of the negative electrode active layer adjacent to the negative electrode tab, thereby reducing the electrode resistance in the first region and improving the capacity loss per unit area on the first surface.
[0158] These results show that the negative electrode for a lithium secondary battery according to the present invention has an excellent effect of suppressing lithium deposition on the surface of the negative electrode active layer during high-rate charging and discharging of the secondary battery, and therefore the lithium secondary battery containing it has a high level of safety and is capable of long-term charging and discharging under high-rate conditions.
[0159] Although the present invention has been described above with reference to preferred embodiments, it will be understood that a person skilled in the art or having ordinary knowledge in the art may make various modifications and changes to the present invention without departing from the spirit and technical scope of the present invention as described in the claims below.
[0160] Therefore, the technical scope of the present invention is not limited to the contents described in the Summary of the Invention of the specification, but is defined by the claims.
Claims
1. a negative electrode active layer provided on at least one surface of a negative electrode current collector and including a carbon-based negative electrode active material; and a negative electrode tab extended to one side of the negative electrode active layer and provided on a non-coated portion of the negative electrode current collector that does not include the negative electrode active layer, The negative electrode active layer is divided into a first region to an n-th region (where 2≦n≦10) having the same length ratio with respect to the entire length based on a thickness direction cross-sectional structure in which a negative electrode tab is provided on one side, and sequentially arranged from a first side portion from which the negative electrode tab is drawn to a second side portion opposite thereto, A negative electrode for a lithium secondary battery, in which the degree of alignment of a carbon-based negative electrode active material represented by the following formula 1 increases from a first region to an nth region: [0010] [0025] [0030] In Formula 1 to Formula 3, S 60/0 is the peak intensity ratio (I0 B/A ) at an X-ray incidence angle of 60° (I60 B/A ) I60 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 60°, I60 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 60°, I0 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 0°, I0 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 0°.
2. The first region of the negative electrode active layer has a degree of alignment (S 60/0 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the ratio of the ionic liquid to the total organic liquid is 0.01 to 1.
0.
3. 2 . The negative electrode of claim 1 , wherein the degree of alignment of the carbon-based negative electrode active material according to the following formula 4 increases from the first region to the nth region: [Formula 4] O.I=I 004 / I 110 In formula 4, I 004 represents the area of the peak representing the (0,0,4) crystal plane in X-ray diffraction (XRD) spectroscopy analysis of the negative electrode active layer, I 110 represents the area of the peak indicating the (1,1,0) crystal plane in X-ray diffraction (XRD) spectroscopic analysis of the negative electrode active layer.
4. 4. The negative electrode for a lithium secondary battery according to claim 3, wherein the carbon-based negative electrode active material contained in the nth region has an alignment degree according to Formula 4 that is 110% to 300% of the alignment degree of the carbon-based negative electrode active material contained in the first region.
5. 4. The negative electrode for a lithium secondary battery according to claim 3, wherein the first region of the negative electrode active layer has an average degree of alignment of the carbon-based negative electrode active material according to Formula 4 of 0.1 to 0.
6.
6. 4. The negative electrode for a lithium secondary battery according to claim 1, wherein the negative electrode active layer has a gradient in which the degree of alignment of the carbon-based negative electrode active material increases from the first region to the nth region.
7. 4. The negative electrode for a lithium secondary battery according to claim 1, wherein the degree of alignment of the carbon-based negative electrode active material increases stepwise from the first region to the nth region in the negative electrode active layer.
8. The first region of the negative electrode active layer has a ratio (I 004 / I 002 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the ratio of the ionic strength of the negative electrode to the total ionic strength of the lithium secondary battery is 0.04 or more.
9. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the carbon-based negative electrode active material comprises at least one of natural graphite and artificial graphite.
10. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the carbon-based negative electrode active material has a sphericity of 0.75 or more.
11. A lithium secondary battery comprising an electrode assembly including a positive electrode, the negative electrode according to claim 1, and a separator disposed between the positive electrode and the negative electrode.
12. The lithium secondary battery according to claim 11, wherein the positive electrode comprises a positive electrode active layer provided on at least one surface of a positive electrode current collector and including one or more positive electrode active materials selected from lithium metal oxides represented by the following Chemical Formula 1 and Chemical Formula 2: [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O 2 [Chemical formula 2] LiM 2 p Mn 1-p O 4 In the above Chemical Formula 1 and Chemical Formula 2, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, and v are each in the range of 1.0≦x≦1.30, 0.5≦y<1, 0<z≦0.3, 0<w≦0.3, 0≦v≦0.1, and y+z+w+v=1; M 2 is Ni, Co or Fe, p is in the range of 0.05≦p≦1.
0.
13. The positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 , LiNi 0.6 Co 0.2 Mn 0.2 O 2 , LiNi 0.9 Co 0.05 Mn 0.05 O 2 , LiNi 0.6 Co 0.2 Mn 0.1 A 0.1 O 2 , LiNi 0.6 Co 0.2 Mn 0.15 A 0.05 O 2、 LiNi 0.7 Co 0.1 Mn 0.1 A 0.1 O 2 , LiNi 0.7 Mn 1.3 O 4 , LiNi 0.5 Mn 1.5 O 4 , LiNi 0.3 Mn 1.7 O 4 , LiFePO 4 , LiFe 0.8 Mn 0.2 P.O. 4 , and LiFe 0.5 Mn 0.5 P.O. 4 The lithium secondary battery according to claim 12, comprising one or more of the following:
14. The lithium secondary battery according to claim 11, wherein the electrode assembly is a stacked type electrode assembly, a zigzag type electrode assembly, or a zigzag-stack type electrode assembly.
Citation Information
Patent Citations
Secondary battery
JP2014137879A
Nonaqueous electrolyte secondary battery
JP2016066426A
Electrode Assembly Having Insulating Material Added on Outermost Surface and Secondary Battery Comprising the Same
KR1020150028457A
Insulating Composition for Electrode of Secondary Battery and Electrode Comprising Electrode Tab Coated by the Same
KR1020160125720A